The Case Study of the Characteristic Analysis and Reinforcement Measures of RC Diaojiaolou Structures Under Different Seismic Intensities - Wenwu Zhong; Zhile Shu; Wenkai Feng; Xin Zhang; Xueye Ma; Zheng Fei (Buildings)
China is strengthening the construction of the disaster resistance capacity of its mountain buildings, which increases the demand for RC Diaojiaolou reinforcement technology. In this paper, the performance of RC Diaojiaolou structures (unreinforced and carbon-fiber cloth-reinforced) in an earthquake is studied by a physical model test. The results show that carbon-fiber cloth can effectively improve the seismic capacity. The natural vibration period and acceleration- and displacement-increment coefficients of DF and CDF conformed to the exponential law. The damage process can be divided into three stages: DS, YS, and PS. After reinforcement, the development law of the average value of the acceleration-increment coefficient changed from the N type to the V type, and the development law of the average value of the displacement-increment coefficient changed from the concave type to the V type. The Diaojiaolou was the least affected by the acceleration at I. The displacement deformation of DF was the least affected by the seismic waves at DZ1. The displacement deformation of CDF was the least affected by the seismic waves at I. These findings provide a theoretical basis for the seismic design of mountain Diaojiaolous.